HSQL Database - Septian Rheno Widianto; I Putu Eka Warmayudha (Institute of Computer Science (IOCS), 2020)
HSQLDB (Hyper SQL Database) is one of database application commonly use for management system in Java. It offers memory and this based on table. As a database, HSQLDB offers a small and quick database that provides server mode and embedded mode. In HSQLDB distribution provided additional tools such as a mini web server, tools for query and management, as well as some examples of the use HSQLDB.